Misleading zinc deficiency diagnose in pome fruit and inappropriate use of foliar zinc sprays - Sanchez, Enrique Eduardo; Righetti, Timothy L. (ISHS, 2025)
Trabajo presentado al International Symposium on Foliar Nutrition of Perennial Fruit Plants, Merano (Italia), 2001